An investigation of thermodynamic states during high-pressure fuel injection using equilibrium thermodynamics. (June 2015) - Qiu, Lu; Reitz, Rolf D.
Graphical abstract: Highlights: A thermodynamically consistent framework to investigate mixture states is formulated. It is shown that calculations without considering phase change are misleading. Subcritical mixing exists though the ambient conditions are supercritical. Two-phase mixtures are produced further lower the system free energy. Abstract: A numerical investigation of mixing processes between an injected fuel (an n -alkane) and a chamber inert gas (nitrogen) was carried out for high-pressure fuel injection. The objective is to determine conditions for the coexistence of both liquid and gas phases under the typical ambient conditions encountered in diesel engines. A phenomenological investigation was built by coupling phase stability analysis with the energy conservation equation. Phase changes (including separation and combination) are predicted to occur so as to yield the lowest Gibbs free energy. It is also shown that predicted states without considering phase transitions can be very different from the corresponding thermodynamically correct states. By comparing four n -alkane/nitrogen mixtures it is shown that the lower limit of the two-phase region occurs at similar temperatures. However, heavy n -alkane/nitrogen mixtures have a larger upper limit, and phase separation occurs at higher temperatures. The present model predicts the existence of multiple phases locally in the dense spray jet under high temperature and pressure ambient conditions due to the significant reduction of the mixture temperature caused by vaporization and cooling.